Amoscritura: «cuerpos atrabesados». Somatología poética de Mario Martín Gijón - Śmiłek, Ewa (Romanica Silesiana, 2021)
The body, although not presented in a direct way, connects the two main themes of Rendicción (2013), the second volume of poetry by Mario Martín Gijón. Based on the theory of José Enrique Finol (presented in the work La corposfera. Antropo-semiótica de las cartografías del cuerpo, 2015), I carry out an analysis of how the corporeality is depicted in the poetry of Martín Gijón. In the said poetry book, the body has not only obtained the status of the object (linked to the themes of love and eroticism), it has also become an assistance of the artistic activity. In this way, the poetry is embodied (Merleau-Ponty, 1993), the word is a living body with all its creative powers.